Translation of the FMR1 mRNA is not influenced by AGG interruptions - Ludwig, Anna L. (Oxford University Press, 2009)
The fragile X mental retardation 1 (FMR1) gene contains a CGG-repeat element within its 5′ untranslated region (5′UTR) which, for alleles with more than ∼40 repeats, increasingly affects both transcription (up-regulation) and translation (inhibition) of the repeat-containing RNA with increasing CGG-repeat length. Translational inhibition is thought to be due to impaired ribosomal scanning through the CGG-repeat region, which is postulated to form highly stable secondary/tertiary structure. One striking difference between alleles in the premutation range (55–200 CGG repeats) and those in the normal range (<∼40 repeats) is the reduced number/absence of ‘expansion stabilizing’ AGG interruptions in the larger alleles. Such interruptions, which generally occur every 9–11 repeats in normal alleles, are thought to disrupt the extended CGG-repeat hairpin structure, thus facilitating translational initiation. To test this hypothesis, we have measured the translational efficiency of CGG-repeat mRNAs with 0–2 AGG interruptions, both in vitro (rabbit reticulocyte lysates) and in cell culture (HEK-293 cells). We demonstrate that the AGG interruptions have no detectable influence on translational efficiency in either a cell-free system or cell culture, indicating that any AGG-repeat-induced alterations in secondary/tertiary structure, if present, do not involve the rate-limiting step(s) in translational initiation.